Knowledge, practice, and training of pediatricians about early childhood caries in Bhubaneswar - Sonali Mallick; Shilpashree Komarla Balaji; Manjunath Chandraiah; Archana Krishnamurthy; Shabana Achapatira Ganesh; Rekha Shantha Venkatesh (Wolters Kluwer Medknow Publications, 2016)
Introduction: Early childhood caries (ECC) is one of the rapidly emerging oral health problems requiring anticipatory guidance. Pediatricians are in the unique and ideal position to advice parents about the prevention and treatment of ECC in their children. Aim: To assess the knowledge, practices, and training regarding ECC and infant oral health care among pediatricians in Bhubaneswar city, Odisha, India. Materials and Methods: A cross-sectional study was conducted among 100 pediatricians in Bhubaneswar city using a self-administered questionnaire. Analysis of variance and Student's t-test were used to find the significance of study parameters. Any value ≤0.05 was considered to be statistically significant. Results: Knowledge about ECC and child oral health was found to be significantly higher among male pediatricians (P = 0.03) and those practicing in urban localities (P = 0.007). Confidence of diagnosing (P = 0.006) and practice patterns (P = 0.003) was found to be significantly higher with increasing hours of patient care per week. Conclusions: Most of the pediatricians had better knowledge were confident and performed better practices.